REPAF: INOVASI TEKNOLOGI BERBAHAN BAKU TAILING BAUKSIT SEBAGAI PENYERAP ASAP KEBAKARAN HUTAN DI RIAU - Sasa Aulia (JURNAL PELITA KOTA, 2023)
Forest fires are the main cause of Indonesia being in fourth place as the country that contributes the highest carbon emissions in the world. To overcome and reduce the impact of forest problems in Indonesia, especially in Riau, an innovation in managing carbon emissions effectively and efficiently is required. Therefore, the proposed innovation is a smoke treatment system due to forest fires that utilizes bauxite waste. This system is called REPAF, which is an air cleaning technology innovation that utilizes synthetic zeolite from the processing of bauxite tailings as an adsorbent of CO2 gas. The research method includes the calculation of energy consumption and analysis of the economic feasibility of using REPAF. The result of the study show that bauxite tailings is able to absorb CO2 gas with an absorption capacity of 6.4 mmol/g zeolite, when compared to zeolite made from active natural ingredients with a CO2 absorption capacity of 1,165 mmol/g zeolite, has a higher CO2 absorption effectiveness. Energy consumption is estimated to be around 7,142×105 kJ during the caustic fusion process. REPAF can contribute to reducing gas emissions in the air, particularly CO2 gas. Economic analysis shows there is a ROI and profits from the sale which is about a year after installation of REPAF. This system also can reduce environmental problems by bauxite waste while creating clean air so that it is expected to reduce carbon emissions by 29% and realize points 3 and 13 of 2030 SDGs.